Analysis of Figurative Language Used in Selected Song Lyrics of Arctic Monkeys in "Am" Album - Rahmad Dede Asriadi; Andi Muhammad Irawan (English Language and Literature, 2022)
This study aimed to find the types of figurative languanges used in selescted song lyrics in Arctic Monkey “AM” album. The Figurative Language found in six songs lyric in AM album. There were "R U Mine?", "Do I Wanna Know?", "Why'd You Only Call Me When You're High?", "One for the Road", "Arabella", and "Snap out of It" songs lyric. This research aimed to show how language can be so in many forms. This study showed how many figurative language and language can be in so many ways to express. This research used qualitative method as a way to analyze figurative language in selected song's lyrics from the album “AM” by Arctic Monkeys. The data in this research used collections of words within their categories of figurative language from Arctic Monkeys’ song lyrics. The result of this study showed types of figurative languages and most used types of figurative languages in selected song by Arctic monkey. There were five types of figurative languages that found in song lyric by Arctic Monkey AM album. There were metaphor, simile, hyperbole, metonymy and synecdoche.